2015
DOI: 10.1177/1745691614568482
|View full text |Cite
|
Sign up to set email alerts
|

How Can Intergroup Interaction Be Bad If Intergroup Contact Is Good? Exploring and Reconciling an Apparent Paradox in the Science of Intergroup Relations

Abstract: The outcomes of social interactions among members of different groups (e.g., racial groups, political groups, sexual orientation groups) have long been of interest to psychologists. Two related literatures on the topic have emerged—the intergroup interaction literature and the intergroup contact literature—in which divergent conclusions have been reported. Intergroup interaction is typically found to have negative effects tied to intergroup bias, producing heightened stress, intergroup anxiety, or outgroup avo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
164
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 163 publications
(169 citation statements)
references
References 130 publications
(284 reference statements)
5
164
0
Order By: Relevance
“…Similarly—but contrary to their findings for disadvantaged groups—Reimer et al () found that only positive (and not negative) intergroup contact promoted LGBT activism among heterosexuals. Consistent with this, when group differences are recognized, and when contact involves repeated positive interactions (consistent with reaching a contact threshold, see MacInnis & Page‐Gould, ), intergroup contact is associated with heightened collective action motivation among advantaged group members (Vezzali et al, ).…”
Section: Intergroup Contact and Collective Actionmentioning
confidence: 77%
See 3 more Smart Citations
“…Similarly—but contrary to their findings for disadvantaged groups—Reimer et al () found that only positive (and not negative) intergroup contact promoted LGBT activism among heterosexuals. Consistent with this, when group differences are recognized, and when contact involves repeated positive interactions (consistent with reaching a contact threshold, see MacInnis & Page‐Gould, ), intergroup contact is associated with heightened collective action motivation among advantaged group members (Vezzali et al, ).…”
Section: Intergroup Contact and Collective Actionmentioning
confidence: 77%
“…Upon reaching a contact threshold as identified by MacInnis and Page‐Gould (), intergroup contact produces largely positive attitudinal outcomes in the form of reduced prejudice. As demonstrated above, there is growing evidence supporting this proposition.…”
Section: The Mixed Outcomes Of Intergroup Contact: Why Does This Paramentioning
confidence: 97%
See 2 more Smart Citations
“…While dissimilarity can give rise to anxiety during intergroup interactions, the anxiety-producing aspects of dissimilarity are less relevant in diverse contexts where intergroup contact is both frequent and benign. Indeed, after people experience a certain number of benign intergroup interactions they may cross a "contact threshold" wherein subsequent intergroup interactions reduce prejudice rather than increase anxiety (MacInnis & Page-Gould, 2015). Thus, in keeping with the predictions of social identity theory, we anticipate that emphasizing intergroup dissimilarity will enhance intergroup interactions and we test this assumption in the context of an ethnically diverse university campus: The University of Toronto, Scarborough.…”
Section: Similarity In Social Versus Personal Identitiesmentioning
confidence: 86%